Closing the digital divide: education telecommunications systems and possibilities in Western Australia - Trinidad, Sue (ACEC, 2006)
The research reported in this paper considers the current telecommunications network for the three education systems of state, independent and catholic schools in Western Australia and Queensland as well as drawing on the personal experiences of teachers in these systems as the government attempts to close the digital divide with its Networking the Nation directives. While email and Internet facilities have greatly improved in rural, regional and remote areas can these systems support every day school use of the Internet and what are the opportunities for advanced telecommunications usage like video conferencing? This paper discusses the possibilities and issues.